EFFECTIVENESS OF AUTOMATED DISPENSING MACHINE (ADM) TO REDUCE THE EVENTS OF DISPENSING ERROR ON MEDICATION ERROR IN INCREASING PATIENT SAFETY: Literature Review - WIDIASTUTI, ZENI (Journal of health research and technology, 2023)
Background: patient safety is one of the main things in providing health services in hospitals. Medication error is one frequent incidents that could harm the patient. Dispensing error is one of the stages in medication errors that can be caused due to high workload, inadequate number of staff, LASA medication, drug packaging that is similar or almost the same, LASA drug storage system, and environmental factors such as distractions and interruptions. Aim: to determine the effectiveness of the Automated Dispensing Machine (ADM) for reduce the incidence of dispensing errors in medication errors to improve patient safety. Methods: this study uses a literature review study by using various journal databases, such as Google Scholar, Science Direct and ProQuest, with journal spanning the last five years. Results: study was shows that the implementation of the Automated Dispensing Machine (ADM) is effective reduce the incidence of dispensing errors in medication errors by being integrated with barcode system and hospital information system. This article can used a refrence in research on the effectiveness of ADM for reduce the incidence of dispensing errors in medication errors.